2015
DOI: 10.1371/journal.pone.0118330
|View full text |Cite
|
Sign up to set email alerts
|

Primates Decline Rapidly in Unprotected Forests: Evidence from a Monitoring Program with Data Constraints

Abstract: Growing threats to primates in tropical forests make robust and long-term population abundance assessments increasingly important for conservation. Concomitantly, monitoring becomes particularly relevant in countries with primate habitat. Yet monitoring schemes in these countries often suffer from logistic constraints and/or poor rigor in data collection, and a lack of consideration of sources of bias in analysis. To address the need for feasible monitoring schemes and flexible analytical tools for robust tren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
48
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 38 publications
(52 citation statements)
references
References 41 publications
(70 reference statements)
4
48
0
Order By: Relevance
“…Considering population trends from other primates in the same forests, it is likely that there may have been a decline and that the population in the Uzungwa Scarp continues to be at risk of further decline. Populations of primates in Mwanihana have shown to be stable in recent surveys and the active protection measures to be efficient (Beaudrot et al, ; Rovero et al, , ), and although Rovero et al () detected a potential decline in mangabey abundance between surveys in 2004–2005 and 2007–2008 and a survey in 2009, the visual line transect method used was highlighted as inefficient for the mangabey and results to be taken with caution. For the Uzungwa Scarp however, studies report a decline for several primate species (Rovero et al, , ).…”
Section: Discussionmentioning
confidence: 99%
“…Considering population trends from other primates in the same forests, it is likely that there may have been a decline and that the population in the Uzungwa Scarp continues to be at risk of further decline. Populations of primates in Mwanihana have shown to be stable in recent surveys and the active protection measures to be efficient (Beaudrot et al, ; Rovero et al, , ), and although Rovero et al () detected a potential decline in mangabey abundance between surveys in 2004–2005 and 2007–2008 and a survey in 2009, the visual line transect method used was highlighted as inefficient for the mangabey and results to be taken with caution. For the Uzungwa Scarp however, studies report a decline for several primate species (Rovero et al, , ).…”
Section: Discussionmentioning
confidence: 99%
“…Despite these trends, protected areas can and do provide long-term sanctuary for wildlife. For example, a study in the Udzungwa mountains of Tanzania showed that colobine primate populations were stable in the protected areas but declined severely in the unprotected forests ( 120 ). An 8-year study (2007–2014) using camera traps to annually monitor terrestrial mammals and birds in 15 protected areas in the Neotropics, Africa, and Southeast Asia showed strong evidence of stability and even increases in populations, including those of 23 primate species (19 cercopithecines in Africa and Asia, 3 African apes, and 1 lemur) ( 121 ).…”
Section: Addressing Conservation Needsmentioning
confidence: 99%
“…It includes taking advantage of global telecommunication systems and wireless Internet, satellite- and airborne-based imagery, drone technology, ever more powerful handheld devices (for example, smart phones and tablets), and camera traps (Supplementary Text) ( 120 , 128 ). Combined with geographic information system and ground surveys, some of this technology has been used in evaluating sustainable land-use spatial planning and human-primate conflicts [for example, Javan gibbons ( Hylobates moloch )] ( 129 ) and in providing case-by-case assessments of species vulnerability to climate change, as shown for Borneo’s orangutans (Supplementary Text) ( 80 ).…”
Section: Addressing Conservation Needsmentioning
confidence: 99%
See 1 more Smart Citation
“…3, Fig. 9) (Mascia et al, 2014;Rovero et al, 2015;Spracklen et al, 2015). Due to illegal 806 activity in the Brazilian Amazon, natural resource reduction is pervasive.…”
mentioning
confidence: 99%